Factors Of Social Inclusion Of The Elderly In Belgrade - Vesić, Zoran; Perišić, Natalija D.; Jakšić, Ivana (Sociološki pregled, 2020)
Social inclusion and social exclusion of the elderly belong to the concepts the operationalization of which has started recently. The objective of this paper is to analyze the factors of social inclusion of the elderly who live in Belgrade. Therefore, a research, using a questionnaire, which included 781 elderly persons living in Belgrade, was conducted in 2019. The dimensions of their health, living standard and financial situation, as well as the quality of life and social participation, were in the focus of the research. Basic findings point to a negative correlation between years of life and all measured outcomes; a positive correlation between their education and subjective assessment of the quality of life and objective measure of social participation in the community; as well as an absence of gender differences in dependent variables, except for the mobility.